(untitled) (UNIZIK Journal of Educational Management and Policy, 2024)
The study investigated autonomous and controlled organizational climate as a predictor of lecturers’ job commitment in public universities in Delta State, Nigeria. Two research questions guided the study and two null hypotheses which were tested at 0.05 level of significance. Correlation research design was adopted for the study. The population of the study comprised all the 2,585 lecturers in all the five public universities in Delta State, Nigeria. A sample size of 766 lecturers was drawn for the study using proportionate sampling technique. A researcher developed instruments titled ‘‘Autonomous and Controlled Organizational Climate Scale (ACOCS)’’ and ‘‘Lecturers Job Commitment Scale (LJCS)’’ were used for data collection. The instruments were validated by three experts, two from the Department of Educational Management and Policy, and one from the Department of Educational Foundations, Nnamdi Azikiwe University. Cronbach alpha was used for a test of internal consistency of the instrument and it yielded overall reliability coefficients of, 0.80 and 0.77 for the clusters A and B of ACOCS respectively with the overall reliability index being 0.79, while coefficient value of 0.82 was obtained for LJCS. The researchers together with five research assistants collected data for the study using the direct approach method and 98% return was recorded. Simple regression was used to answer the research questions and test hypotheses 1 and 2. The findings of the study revealed among others that autonomous climate is a strong and significant predictor of lecturers’ job commitment in universities in Delta State. Further results indicated that controlled climate is a low and significant predictor of lecturers’ job commitment in universities in Delta State, Nigeria. Based on the findings, it was recommended among others that Directorate of Research, Innovation and Information Technology of National Universities Commission should develop hands and promote the publication of journals and books based on the findings of the study to serve as the blueprint for modifying the existing controlled climate to improve job commitment of lecturers.